Compatibility between Qur’anic Education Stories in Elementary Stage and Aspects of Education - Maryam Nassaj; Esmat Hemati (پژوهش در آموزش معارف و تربیت اسلامی)
Nowadays, storytelling is an effective means in education and upbringing because it can convey important educational points from different aspects. In this regard, the purpose of the present research is to review and analyze to what extent stories in the Qur’anic Course Book through 6 stages of elementary school are based on 6 aspects of the fundamental transformation document of education and upbringing. The research method is descriptive content analysis and the obtained results were analyzed by Shannon Entropy. The results showed that in the Qur’anic Education Book of the elementary school, 22 stories are mentioned which deal with the following aspects: 19 cases about beliefs, prayers, and morality, 14 cases about social and political fields, 4 cases about aesthetic and artistic fields, 2 cases about biological and bodily fields, 2 cases about economic and professional fields, and 1 case about scientific and technological fields. Among aspects under review, beliefs, prayers, and morality with the data load of 0.97 and the importance factor of 0.30 have gained the highest attention while scientific and technological aspects with the data load of 0.0003 and the importance factor of 0.0009 have gained the least attention.